Visual outcome with sclerocorneal contact lens in case of a pellucid marginal degeneration - K Husna (Kerala Journal of Ophthalmology, 2023)
A 40-year-old male presented with progressive dimness of vision in right eye. Slit-lamp microscopy revealed features of pellucid marginal degeneration in right eye. Corneal topography showed “crab-claw” pattern of thinning. His visual acuity in right eye improved well with sclerocorneal contact lens.